Deformación elástica y módulo de elasticidad en arcillas expansivas mediante ensayos de laboratorio - Rosales Asto, E.A. (2023)
Expansive soils have special properties and it is difficult to find resistance parameters; Angle of internal friction and cohesion by the Morh-Coulomb theory, therefore it is necessary to evaluate the elastic constants that allow us to calculate the settlement and the admissible load of these soils. The present investigation has as objectives to determine the elastic deformation and the elasticity modulus in expansive clays, taking three samples from San Ignacio - Cajamarca (M-1, M-2, M-3) and one from Pavayacu - Loreto (M-4). To determine these parameters, tests were carried out in the Soil Mechanics Laboratory of the UNALM, free expansion tests were carried out; and one-dimensional consolidation tests will be carried out on the expanded samples. For a specific charge, charge and discharge cycles will be carried out until a hysteresis is generated where the charge and discharge curves overlap, forming a line that corresponds to an elastic behavior. As an artifice, a parallel to the last hysteresis was drawn at the origin of the consolidation curve, which corresponds to the tangent of the consolidation curve. Elastic strain and plastic strain are determined independently. The values ​​obtained from the modulus of elasticity (Es) are within the ranges of 41.8 kg/cm2 to 70.1 kg/cm2, these values ​​classify the soil as soft clay.